Effectiveness of microcredit financing in enhancing well-being of micro enterprise entrepreneurs in Selangor, Malaysia - Mohd Tammili, Fatin Najiha (2017)
Poverty has been one of the pressing issues in developing countries like Malaysia. Microcredit institutions are effective tool for poor people can move out from poverty by improving their lives and giving them the provision of fund for their business. Amanah Ikhtiar Malaysia (AIM) was the first microcredit finance institution and one of the dominant players contributing to the poverty eradication in Malaysia by providing microcredit to the poor. Therefore, issues relating to the effectiveness of AIM on the well-being of AIM respondents need to be investigated.